The Use Of Song In The Introduction Of English Vocabulary In Elementary School - Indah Ratih Nawangwulan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this paper is to improve the ability of elementary school students inprocessing vocabulary in learning English. The media used by the teacher in thisdiscussion is by using the media song.The learning carried out must be related to thesubject matter and adapted to the age of the students. For example, Bingo, One and One,Good Morning, Happy and you know it clap your hands, One Two Three.The use of songsin learning English can be said to be the right way because in addition to motivatingstudents in learning, fostering a cheerful atmosphere in learning, this activity is also usefulin developing vocabulary, improving students' listening and pronunciation skills. Besidesthat, it can also improve student learning outcomes in English, and with the media,children's songs will be easy to accept the vocabulary taught. Songs can be used in learningactivities for the four aspects of English, namely listening, reading, speaking, and writing.